Genetic genealogy and the potential to reconnect transtemporal ties (Research, Society and Development, 2022)
Genealogical research has been impacted by the recent acceleration in the pace of change, mainly thanks to the contribution coming from genetics through ancestry testing. The results of this impact reverberate in new dimensions of both ancestral and parental genealogy in parallel with severe impacts on the institution of family. The perennial character of the family bond, which even despite the diversity of family ties, seats in parenthood the quality of an almost timeless and absolutely universal phenomenon, receives the valuable contribution of genetic and athropological research. The present study catches the recent increments in genetics and institution family by genetics related to health, reflected in the light of Law, promoting ways for parenting and identity in the face of this definition of studies of social dimensions of being-in-the-world. Thus, it presents the remote unveiling that enables new family and parental encounters and constructions, including Brazilian public actions that can enhance these results as a structured public policy.